Longitudinal relationships between strength and static jump asymmetries in collegiate soccer players - Painter, K.; Rodriguez-Castellano, L.; Carroll, K.; Stone, M. (The Journal of Strength and Conditioning Research, 2021)
Several studies have linked asymmetries in bilateral jump performance to a potential risk of injury. Asymmetries have also been linked to maximal strength, suggesting that weaker athletes have greater asymmetry than stronger athletes. Purpose: To investigate the association between maximal strength and static jump (SJ) bilateral asymmetry in collegiate soccer players, along with the change over time. Methods: Athlete monitoring data from male (M, n = 9) and female (F, n = 9) NCAA Division-I soccer players were considered for this analysis. This retrospective analysis included SJ and isometric mid-thigh pull (IMTP) assessments and was approved by the university's Institutional Review Board. Baseline data (PRE) were collected in the pre-competitive period (i.e., fall semester). Athlete data were collected again in the pre-competitive period (POST), 2 years after the initial collection. In the interim, athletes participated in both soccer and strength & conditioning activities consistently. Each athlete followed the same standardized warm-up protocol during each testing session, then performed 2 maximal effort trials of both the SJ and IMTP. Symmetry index score (SI) was calculated using unilateral peak force values during the take-off phase of the jump (Eq. 1). To assess maximal strength, allometrically-scaled isometric peak force (IPFa) was calculated from the IMTP test. Data from the 2 maximal effort trials were averaged together for analysis. Equation 1: SI = (Left Force Value - Right Force Value/Left Force Value + Right Force Value) × 100 To analyze results, a 2 × 2 mixed design ANOVA (group × time) was used. When statistically significant main effects were observed, a Holm-Bonferroni post hoc adjustment was used. Pairwise comparisons were further assessed using Cohen's d effect sizes (ES). Pearson's correlations were used to quantify the relationship between the SI and IPFa change scores. Results: Mean IPFa values increased from PRE (M = 207.1 ± 31.3 N/kg² 3; F = 145.8 ± 28.1 N/kg² 3) to POST (M = 218.5 ± 21.7 N/kg² 3; F = 169.3 ± 12.8 N/kg² 3). Statistically significant main effects for time (PRE-POST) and group (M and F) for IPFa were observed (p = 0.016, p < 0.001; respectively) with a moderate change magnitude (d = 0.635). Mean POST SI (2.9 ± 3.4%) indicated greater asymmetry compared to PRE (1.3 ± 3.0%). PRE to POST differences in SI were statistically significant (p = 0.012) with no statistical differences between M and F. Static jump heights were significantly different between M and F (p < 0.001), but no significant changes occurred from PRE to POST. Moderate negative correlations were found between IPFa and absolute SI differences (r = -0. 472, p = 0.048). Conclusions: Moderate correlations in IPFa and SI changes suggest strength does play a role in deterring asymmetry. However, increases in SI from PRE to POST does support the possibility of functional asymmetries developing in soccer players. While IPFa improved, F had a greater change from PRE to POST (d = 0.602) than M (d = 0.292), possibly due to the lower baseline levels of strength. Overall, more in-depth longitudinal observations are needed to ascertain the true relationship between SI and IPFa across time in soccer players. Practical Applications: Soccer athletes are prone to develop some functional asymmetries. Further development of strength and non-dominant side usage in both M and F soccer players may reduce a potential risk of injury from asymmetry over time.